Utilização do método de opções reais para análise de investimentos em infraestrutura: o caso do trem de alta velocidade (TAV Brasil) - Couto, José Carlos Maltez do (2013)
The project of high-speed train that will transport passengers between the two largest cities of the country is a major investment Acceleration Plan (PAC). After the failure shown in the first bidding process, due to the absence of a proposal from private investors, the Federal Government decided to amend its participation in the investment plan, in addition, this second attempt, scheduled for September 2013, the Government reported that reduce the minimum amount of grant to be paid by the concessionaire winner at 3.2%, which will increase the state's investment of approximately R$ 900 million. The public sector search through the measures outlined, increasing the attractiveness of the project and reported that may increase its stake in the project, 45% of the shares of the SPE control the TAV to about 80%. This study discusses the granting of a guarantee of minimum demand of passengers, the results obtained through the methodology of real options indicate that they can generate an increase in NPV of 22.2% and a cost to the public purse of only 2.86 % of total investment in the project.